ROLE OF BISHOP KOOP PROCEDURE IN MANAGEMENT OF JEJUNOILEAL ATRESIA – A SINGLE CENTER STUDY - JAMEEL, M; CHAUDHARY, MA; JAMIL, A; ZAFAR, S; VALID, R (Biological and Clinical Sciences Research Journal, 2024)
Jejunoileal atresia is a significant congenital condition requiring surgical intervention. The Bishop Koop procedure has been a notable technique for managing this condition, yet comprehensive evaluations of its efficacy and safety are needed to validate its continued use. Objective: To evaluate the effectiveness of the Bishop Koop procedure in managing jejunoileal atresia. Methods: This cross-sectional study was conducted at the Department of Pediatric Surgery, The Children’s Hospital, PIMS Islamabad, from July 2023 to April 2024. Forty-two patients diagnosed with jejunoileal atresia were clinically evaluated and underwent the Bishop Koop procedure. Post-operative outcomes, including the duration of surgery, time to initiate bowel movements and feeding, and early complications, were recorded. Patients were followed up during their hospital stay to record outcomes of discharge or expiry. SPSS version 29.0 was utilized to identify mortality predictors. All patients received postoperative intravenous antibiotics. Results: Of the 42 neonates treated, 66.7% were successfully discharged, while 33.3% expired, indicating a significant rate of adverse outcomes. The study provides detailed data on surgical durations, recovery times, and complication rates. Conclusion: The findings suggest that the Bishop Koop procedure is a safe and effective surgical option for severe jejunoileal atresia despite the substantial proportion of adverse outcomes. Further studies are warranted to optimize patient selection and procedural techniques to enhance survival rates.